Atomic Engineering Catalyzed Redox Kinetics of NixCo1‐x(OH)2 on Nanoporous Phosphide Electrode for Efficient Ni‐Zn Batteries. Issue 19 (7th April 2022) - Tian, Jiaxin; Peng, Ming; Luo, Min; Lan, Jiao; Zhang, Yanlong; Tan, Yongwen
Abstract: Aqueous nickel‐zinc (Ni–Zn) batteries with excellent safety and environmental benignity are promising candidates for sustainable energy storage. However, the inferior conductivity and inevitable phase transition of trditional Ni‐based cathodes limit the redox kinetics and lead to restricted electrode specific capacity and device energy density. Here, a Nix Co1‐x (OH)2 electrode doped with Pd, Ag, and Au atoms is constructed for catalyzing the redox kinetics on the conductive nanoporous phosphide. Density functional theory calculations and experimental results reveal that the introduction of the Ag atomic dopants can effectively modulate the electron structure and optimize the OH − adsorption energy, thereby accelerating the catalyzed redox kinetics of Nix Co1‐x (OH)2 by the facilitated charge transfer at the active sites around metal dopants. Consequently, the assembled Ni–Zn battery delivers an ultrahigh power density of 7.85 W cm −3 and energy density of 49.53 mW h cm −3, with a long‐term cycling stability. The cooperation of atomic catalysis and redox kinetics will inspire more exploration of efficient energy materials and devices. Abstract : A Nix Co1‐x (OH)2 electrode with atomic dopants is constructed to enhance the redox kinetics on conductive nanoporous phosphide. The atomic Ag dopants can effectively modulate the electronic structure, optimize the OH − adsorption energy, and accelerate the interfacial redox kinetics of Nix Co1‐x (OH)2 via catalysis, resulting in a highly efficient nickel‐zinc (Ni–Zn) battery.